The Effect of a Flipped Classroom with Youtube Integration Towards Students’ Listening Skill in SMAN 1 Seririt - Utami, Luh Aprilia; Dambayana, Putu Eka; Budiarta, Luh Gd Rahayu (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study investigated the impact of integrating YouTube into a flipped classroom model to improve students’ listening skills at SMAN 1 Seririt. The aim was to determine whether this strategy significantly improved students’ listening comprehension compared to conventional teaching. This study was motivated by the observed challenges that students faced in comprehending English listening materials using traditional teaching methods. The focus of this study was on the implementation of the flipped classroom approach, where students watched educational videos from YouTube before class, so that class time could be used for interactive and practical activities. Two eleventh-grade classes were selected as the experimental and control groups, using a quantitative method with a quasi-experimental approach. The experimental group received instruction through the flipped classroom method using YouTube videos, while the control group followed traditional instruction. Data were collected through pre-tests and post-tests assessing listening skills and were analyzed using descriptive and inferential statistics, including t-tests. Supported by a medium effect size (Cohen’s d = 0.61), the findings indicated that the experimental group showed statistically significant improvements in listening skills. Thus, integrating YouTube in a flipped classroom setting effectively improved students’ listening comprehension and offered a student-centered, engaging, and flexible learning experience.